Use of the Left Ventricular Internal Dimension at End-Diastole and the Mitral Valve E-Point Septal Separation Ratio in the Prediction of the Left Ventricular Systolic Function (Cardiovascular Journal, 2023)
Background: Rapid assessment of left ventricular ejection fraction (LVEF) may be critical among emergency department (ED) patients. This study examined the predictive relationship between bedside Left Ventricular Internal Dimension at End-Diastole and the Mitral Valve E-Point Septal Separation (EPSS) Ratio to the quantitative calculated LVEF.Methods: A prospective observational study was conducted on a sequential convenience sample of patients, receiving comprehensive Transthoracic Echocardiography (TTE). The current study recruited 100 patients who presented to the Cardiology Clinic of Lab Aid Cardiac Hospital. Echocardiographic examinations were performed to obtain 2D guided M-mode measurements of the LVIDd & EPSS in addition to calculation of conventional, quantitative LVEF. All the measurements were done in the Para-sternal long-axis view.Results: It was found that LVEF determined by EPSS has very significant negative correlation with Calculated LVEF (r=—.766, p